An investigation into the effects of current immunosuppressants and novel compounds on animal models of asthma and delayed type hypersensitivity - McHale, Brendan (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2007)
Asthma is a disease with a worldwide distribution and of increasing prevalence. There are two forms of the disease; intrinsic, which is believed to follow a Th1 cytokine profile and extrinsic, which follows a Th2 response. A problem with many current treatments is the side effects they cause at high doses. For this reason, a number of novel compounds were evaluated in animal models of delayed type hypersensitivity (DTH) and asthma. In extrinsic asthma, an allergen stimulates a Th2 response, IgE production from B cells and mast cell degranulation, causing the release of eicosanoids and various cytokines. This stimulates the recruitment of leukocytes such as eosinophils and neutrophils to the lungs and ultimately leads to hypersensitivity of the airways. Bronchial hyper-reactivity also occurs following leukocyte recruitment in intrinsic asthma although it may follow a Th1 response and has not been shown to involve mast cells or IgE production.
Keywords: Pharmacology, Ph.D.; Ph.D. Trinity College Dublin